Development of an Ornamental Village through the Utilisation of Non-Organic Waste Plastic Bottles into Vertical Garden Flower Pots and Garden Differentiation in Banjargondang Village Lamongan - Moh. Vito Miftahul Munif; Intan Nasidatur Rohma; Muhamad Taufiq Firmansyah (Shof Journal of Social Impact, 2024)
The purpose of this community service activity is to develop a Decorative Village through the Utilization of Non-Organic Waste Plastic Bottles into Vertical Garden Flower Pots and Differentiation in Banjargondang Village Lamongan. The method of implementing activities is carried out through 5 stages, namely observation, planning, making flower pots, planting flowers into pots, and implementing the installation of flower pots in the banjargondang village area. The results of this activity are First, the realization of the ornamental village concept in banjargondang village which makes the village more beautiful, beautiful, green and organized with the arrangement of several flowers at several points in the area. Second, making the village cleaner, the utilization of plastic bottle waste can reduce the amount of plastic waste in the Banjargondang community. Third, increasing public awareness about proper waste management, the management of plastic waste into flower pots has inspired the community to be creative in utilizing plastic waste in the surrounding environment, so that waste will be reduced and well managed.